Overexpression of Pti4, Pti5, and Pti6 in tomato promote plant defense and fruit ripening. (January 2021) - Wang, Yang; Feng, Guodong; Zhang, Zheng; Liu, Ying; Ma, Yilong; Wang, Yingying; Ma, Fei; Zhou, Yu; Gross, Rachel; Xu, Huanhuan; Wang, Ruipeng; Xiao, Fangming; et al.
Highlights: Pti4/5/6 -overexpressed tomato confer enhanced resistance to Pst DC3000. Transgenicis showed accelerated fruit ripening. Overexpression of Pti4/5/6 performed no obvious adverse impact on fruit traits. Pti4/5/6 -overexpressed fruits exhibited increased activities of defense enzymes. Pti4, Pti5 and Pti6 degraded by 26S proteasome. Abstract: Pseudomonas syringae pv. tomato ( Pst ) is a pathogenic microorganism that causes bacterial speck disease and affects tomato yield and quality. Pto is a disease resistant gene for plant to recognize and defense against Pst . Pto interacts with Pti (Pto interacting) proteins, which include three transcription factors, Pti4, Pti5, Pti6, and they were thought to be downstream of Pto-mediated pathway to promote the expression of disease-related genes. In the present work, the overexpression plants of Pti4, Pti5 or Pti6 were obtained by Agrobacterium -mediated transformation in tomato. The Pti4/5/6 -overexpressed lines indicated enhanced expression of pathogenesis-related genes and resistance to pathogenic bacteria Pst DC3000. Meanwhile, the transgenic plants showed that Pti4/5/6 function in ripening but performed no obvious adverse influence on flowering time, seed-setting rate, weight and soluble solids content of fruits. Furthermore, Pti -overexpressed fruits exhibited increased enzymatic activities of phenylalnine ammonialyase, catalase, peroxidase and decreased content of malondialdehyde. Additionally, cell-free and in vivo ubiquitination assay indicated that Pti4, Pti5 and Pti6 degraded by 26S proteasome which suggested that these Pti transcription regulators' functions could be regulated by ubiquitin-mediated post translational regulation in tomato.